أثر وسيلة اليوتوب لقناة بودكاست عربي على فاعلية تعليم اللغة العربية في مدرسة آل عمران باندر سلامت - Hasibuan, Atika Nur Ardila; Nasution, Sahkholid (YASIN, 2025)
This analysis aims to gather statistical data on the impact of using the YouTube media 'Arab Podcast' on the effectiveness of Arabic learning at MTs. Ali Imran Bandar Selamat. The study employs a true experimental design based on a pretest-posttest control group approach. It involves a sample of 58 participants divided into two groups: a specialized group (experimental) and a non-specialized group (control). The results of this analysis demonstrate a significant effect on the classes studying Arabic using YouTube as an instructional tool. The development of the mean scores for pre-test and post-test indicates significance in the specialized group (experimental). Utilizing YouTube facilitates students in mastering language skills in Arabic, such as listening (istima') and speaking (kalam). Based on statistical analysis, YouTube has proven to be an effective tool in Arabic learning, serving as a creative and innovative teaching aid.